Rehabilitation and neuroplasticity in children with unilateral cerebral palsy - Reid, L.; Rose, S.; Boyd, Roslyn (2015)
Cerebral palsy is a childhood-onset, lifelong neurological disorder that primarily impairs motor function. Unilateral cerebral palsy (UCP), which impairs use of one hand and perturbs bimanual co-ordination, is the most common form of the condition. The main contemporary upper limb rehabilitation strategies for UCP are constraint-induced movement therapy and bimanual intensive therapy. In this Review, we outline the factors that are crucial to the success of motor rehabilitation in children with UCP, including the dose of training, the relevance of training to daily life, the suitability of training to the age and goals of the child, and the ability of the child to maintain close attention to the tasks. Emerging evidence suggests that the first 2 years of life are a critical period during which interventions for UCP could be more effective than in later life. Abnormal brain organization in UCP, and the effects of development on rehabilitation, must also be understood to develop new effective interventions. Therefore, we also consider neuroimaging methods that can provide insight into the neurobiology of UCP and how the condition responds to existing therapies. We discuss how these methods could shape future rehabilitative strategies based on the neurobiology of UCP and the therapy-induced changes seen in the brain.